2014
DOI: 10.1586/14737175.2014.928202
|View full text |Cite
|
Sign up to set email alerts
|

The role of subcutaneous infusion of apomorphine in Parkinson’s disease

Abstract: Continuous subcutaneous apomorphine infusion therapy (CSAI) has proved to be effective in advanced Parkinson's Disease patients with motor fluctuations not controlled by oral or transdermal medication. In this clinical setting it competes directly with intrajejunal levodopa and deep brain stimulation (DBS), however randomised controlled comparative studies are lacking. The advantages of CSAI is that it is the least invasive of these three therapeutic options, is reversible, practical to use and has shown signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 95 publications
0
21
0
13
Order By: Relevance
“…In the case of continuous apomorphine infusion, no randomized, double-blind, placebocontrolled studies have been published to date; however, a limited number of small randomized controlled trials as well as data from smaller open-label and observational studies undertaken over several decades have shown efficacy in controlling motor fluctuations, reducing 'off' time, and have suggested an improvement in dyskinesias; these findings have been summarized in a recent review [20].…”
Section: Apomorphine In the Treatment Of Parkinson's Diseasementioning
confidence: 99%
“…In the case of continuous apomorphine infusion, no randomized, double-blind, placebocontrolled studies have been published to date; however, a limited number of small randomized controlled trials as well as data from smaller open-label and observational studies undertaken over several decades have shown efficacy in controlling motor fluctuations, reducing 'off' time, and have suggested an improvement in dyskinesias; these findings have been summarized in a recent review [20].…”
Section: Apomorphine In the Treatment Of Parkinson's Diseasementioning
confidence: 99%
“…The origin of these complications is unknown, but a relationship with the pulsatile dopaminergic stimulation, due to the oral substitute therapy, has been proposed [3]. In a way to give a more stable and physiological stimulation to the dopaminergic receptors, alternative therapy, as continuous subcutaneous infusion of apomorphine, deep brain stimulation (DBS) [4,5], and the continuous intra-duodenal infusion of levodopacarbidopa gel (LCIG) have been tried [6].…”
Section: Introductionmentioning
confidence: 99%
“…Apomorphine has many associated adverse effects, although most are mild and transient, including vegetative (eg, orthostatic hypotension, nausea, vomiting, bradycardia, salivation, sweating), neuropsychiatric, and local reactions (eg, subcutaneous or skin nodules, abscesses, necrosis), in addition to leg edema and livedo reticularis. Hematologic reactions are less common and, although very rare, some events may be life threatening, including DIIHA …”
Section: Discussionmentioning
confidence: 99%
“…Hematologic reactions are less common and, although very rare, some events may be life threatening, including DIIHA. [11][12][13] Drugs are responsible for 12% of all cases of immune hemolytic anemia (IHA). 10 However, DIIHA incidence is probably underestimated.…”
Section: Discussionmentioning
confidence: 99%